Clinical Characteristics and Outcomes of Coronavirus Disease 2019 Among Patients With Preexisting Liver Disease in the United States: A Multicenter Research Network Study (2020)
Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has emerged as a global public health crisis. Liver injury has been reported during the COVID-19 disease progression.1 However, previous studies did not examine in detail the interaction of preexisting liver disease and COVID-19.1 Therefore, we aimed to study the impact of preexisting liver disease on outcomes in a large cohort of patients with COVID-19 in the United States.